Rancang Bangun Sistem Aplikasi Inventory Barang Berbasis Web Pada Yayasan Islam Bahrun Nasirin - Eni Susilowati; Dede Sahrul Bahri (CV. Multi Kreasi Media, 2024)
Technology is very influential to facilitate human work. Of the various kinds of Information System technology plays an important role for a Company or Institution. To realize a good system must have an information system that can support activities within the company. The aim of the research is to provide solutions to existing problems by designing an inventory system, especially at the Bahrun Nasirin Islamic Foundation as an effort to develop information technology. The method used in this research is using the waterfall method. Data collection was carried out using the direct method at the Bahrun Nasirin Islamic Foundation. Data collection was carried out by observing, interviewing, and inputting inventory data based on data obtained from the Bahrun Nasirin Islamic Foundation. The data collection carried out is qualitative. The results and conclusions of this study are the design of a website-based goods inventory system that can be used as a medium that can facilitate the processing of goods procurement data, goods whose residues have expired, damaged goods, lost goods, and reports on goods data inventory. For the design of this system using the programming language PHP, JavaScript, MySQL. UML is used as a model for the design of this website-based sales application.